EVIDENTIARY VALUE OF NARCO- ANALYSIS: AN ANALYSIS OF INDIAN LEGAL POSITION - L Haritha; Sridhar, Pininti; Anishkumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper explores the value of using narco-analysis and its application in the Indian legal system. A method, using drugs administered to an individual to bring him or her into a semi-conscious state, in order to gain information during a criminal investigation. The study examines the constitutionality of the narco-analysis under Article 20(3) and 21 of the Constitution of India and admissibility under Indian Evidence Act, 1872. The involuntary administration of narco - analysis tests has been limited by judicial pronouncements, especially in Selvi v. State of Karnataka. Finally, the paper finds that the use of narco-analysis as an investigative tool and not substantive evidence on its own must be backed up by legally admissible corroborative evidence.